Accuracy of intuition in clinical decision‐making among novice clinicians. (30th November 2016) - Price, Amanda; Zulkosky, Kristen; White, Krista; Pretz, Jean
Abstract: Aims: To assess the reliance on intuitive and analytical approaches during clinical decision‐making among novice clinicians and whether that reliance is associated with accurate decision‐making. Background: Nurse educators and managers tend to emphasize analysis over intuition during clinical decision‐making though nurses typically report some reliance on intuition in their practice. We hypothesized that under certain conditions, reliance on intuition would support accurate decision‐making, even among novices. Design: This study utilized an experimental design with clinical complication (familiar vs. novel) and decision phase (cue acquisition, diagnosis and action) as within‐subjects' factors, and simulation role (observer, family, auxiliary nurse and primary nurse) as between‐subjects' factor. Methods: We examined clinical decision‐making accuracy among final semester pre‐licensure nursing students in a simulation experience. Students recorded their reasoning about emerging clinical complications with their patient during two distinct points in the simulation; one point involved a familiar complication and the other a relatively novel complication. All data were collected during Spring 2015. Results: Although most participants relied more heavily on analysis than on intuition, use of intuition during the familiar complication was associated with more accurate decision‐making, particularly in guiding attention to relevant cues. With the novel complication, use of intuition appeared to hamper decision‐making, particularly for those in an observer role. Conclusion: Novice clinicians should be supported by educators and nurse managers to note when their intuitions are likely to be valid. Our findings emphasize the integrated nature of intuition and analysis in clinical decision‐making.